Presidential Threshold dalam Sistem Presidensiil dan Implikasinya terhadap Fungsi Pengawasan DPR - Sunarto; Eta Yuni Lestari (Universitas Negeri Semarang, 2026)
This study aims to analyze the relationship between the presidential threshold in Indonesia’s presidential system and the effectiveness of the House of Representatives (DPR) in carrying out its oversight function over government policies. The implementation of the presidential threshold, which was intended to strengthen political support for the elected president, has created a practical problem when non-supporting parties tend to join the ruling coalition after the election. This condition weakens the DPR’s oversight function, as the dominance of political compromise reduces the presence of effective opposition in parliament. This research employs a normative legal method using both statutory and conceptual approaches. The primary legal materials consist of constitutional and statutory provisions regulating the presidential system and the oversight authority of the DPR, while secondary materials include books and journal articles written by constitutional law scholars. The results indicate that political stability in a presidential system should not rely on the presidential threshold, but rather on the strength of the checks and balances mechanism between the executive and legislative branches. The Constitutional Court Decision No. 62/PUU-XXII/2024, which declared the presidential threshold unconstitutional, represents an important turning point to reinforce democratic representation and restore the DPR’s oversight function to be more independent, transparent, and accountable.